2021
DOI: 10.51731/cjht.2021.60
|View full text |Cite
|
Sign up to set email alerts
|

Flash Glucose Monitoring Systems in Pediatric Populations With Diabetes

Abstract: Flash glucose monitoring (FGM) is a method of glucose testing where a sensor inserted into the skin continuously measures interstitial glucose levels. It can be used by people with diabetes to inform treatment decisions, such as insulin dosing, as an alternative or complement to blood glucose testing. Evidence of variable quality from 2 randomized controlled trials and 8 non-randomized studies, including those summarized within systematic reviews, suggests that FGM may improve quality of life, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…More recently, CADTH completed a review of the FreeStyle Libre systems in the pediatric T1DM population, 36 concluding that the evidence indicates that the systems may improve QOL, patient satisfaction, diabetes distress, self-efficacy, and frequency of glucose monitoring compared to SMBG. The report noted that findings related to HbA1c, glucose TIR metrics, and adverse events were mixed; but ultimately concluded that the use of either of the FreeStyle Libre systems is associated with improved clinical outcomes in pediatric populations with T1DM.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, CADTH completed a review of the FreeStyle Libre systems in the pediatric T1DM population, 36 concluding that the evidence indicates that the systems may improve QOL, patient satisfaction, diabetes distress, self-efficacy, and frequency of glucose monitoring compared to SMBG. The report noted that findings related to HbA1c, glucose TIR metrics, and adverse events were mixed; but ultimately concluded that the use of either of the FreeStyle Libre systems is associated with improved clinical outcomes in pediatric populations with T1DM.…”
Section: Resultsmentioning
confidence: 99%